ANALISIS KUALITAS PELAYANAN TRANSPORTASI UDARA DI BANDAR UDARA MUTIARA PALU - Afni, Nur (Katalogis, 2013)
This study aims to determine the quality of air transport services In Palu Mutiara Airport Office. The theory used to analyze problems in this study is the theory which cohabited Suhady look at the quality of service indicators Exactly, Fast, Cheap and Friendly. The research method used is Qualitative Research. Informants in this study consists of the Head Office of Palu Mutiara airport and the staff and service users Mutiara Airport Palu. While the techniques of data analysis is data reduction, data presentation, and describe and infer and verify the data. that the quality of services provided Mutiara Airport Palu is not maximized it can be seen from the first: accuracy, precision provided Palu Mutiara Airport service is not right for the services provided are usually frequent delays, Second: Fast. In providing services at Mutiara Airport Palu has not so fast, third: Cheap. Services provided include Palu Mutiara airport is reasonably priced and a fourth: Hospitality means the attitudes providers at Mutiara Airport Palu was friendly enough but still need to be at the level again. While the limiting factor of the quality of service Palu Mutiara Airport is the ability of the Human Resources service provider inadequate forces, and the second is the inadequate facilities available at Mutiara Airport Palu.